Assessment of atmospheric deposition of heavy metals and other elements in operating zone of CHP using moss biomonitoring technique; Journal of International Scientific Publications; Vol. 6, pt. 2 - Rogova N. S. Natalya Sergeevna; Ryzhakova (Rizhakova) N. K. Nadezhda Kirillovna; Merkulov V. G. Viktor Georgievich; Borisenko A. L. Aleksey Leonidovich (2012, 2012)
Title screen